Human fall detection method based on 4D point cloud and track information - Zhou Yang; Li Jianpeng; Wang Zhiyu; Liang Qingzhen (Dianzi Jishu Yingyong, 2024)
In family and medical health monitoring, timely and accurate real-time monitoring of elderly falls is an important topic, and millimeter wave radar has shown great application potential in non-contact fall detection. The traditional method mainly uses the Doppler information obtained by millimeter wave radar as the fall detection feature. However, for some scenarios, such as the distance between the person and the radar or the direction of the fall is perpendicular to the normal of the radar antenna, the effectiveness of the Doppler information feature will be reduced, and the fall detection accuracy will be reduced.